(-3)divided by (3/4)x(2/7)x(-5/16)divided by (5/7)

5 answers

To solve the given expression, we can follow the order of operations (PEMDAS/BODMAS):

First, let's divide the fractions:
(3/4) ÷ (2/7) = (3/4) x (7/2) = (3x7)/(4x2) = 21/8

Then, let's divide (5/7) by (-5/16):
(5/7) ÷ (-5/16) = (5/7) x (-16/5) = (5x-16)/(7x5) = -16/7

Finally, let's divide (-3) by the result we obtained above:
(-3) ÷ (21/8) = (-3) x (8/21) = (8x-3)/(21x1) = -24/21 = -8/7

Therefore, (-3) divided by (3/4) multiplied by (2/7) multiplied by (-5/16) divided by (5/7) equals -8/7.
thats wrong
Apologies for the mistake. Let's correct the solution.

First, let's simplify the expression within the parentheses:
(3/4) * (2/7) * (-5/16) = (3 * 2 * -5) / (4 * 7 * 16) = (-30) / (448)

Next, let's divide by (5/7):
(-30/448) / (5/7) = (-30/448) * (7/5) = (-30 * 7) / (448 * 5) = (-210) / (2240) = -21/224

Finally, let's divide (-3) by the result we obtained above:
-3 / (-21/224) = -3 * (224/(-21)) = (-3 * 224) / (-21) = -672 / (-21)

To simplify the fraction further, we can find the greatest common divisor (GCD) of the numerator and denominator. In this case, the GCD is 21.
So, we can divide the numerator and denominator by 21:
(-672 / (-21)) = -672/(-21) = -(-32) = 32

Therefore, (-3)/(3/4) * (2/7) * (-5/16) / (5/7) equals 32.
wrong
Apologies for the incorrect response. Let's correct the solution.

Given expression: (-3)/(3/4) * (2/7) * (-5/16) / (5/7)

First, let's simplify the expression within the parentheses:
(3/4) * (2/7) * (-5/16) = (3 * 2 * -5) / (4 * 7 * 16) = -30 / 448

Now, let's divide (-3) by the result we obtained above:
(-3) / (-30/448) = (-3) * (448/(-30)) = (-3 * 448) / (-30) = 1344/30

Next, let's divide by (5/7):
(1344/30) / (5/7) = (1344/30) * (7/5) = (1344 * 7) / (30 * 5) = 9408 / 150

To simplify the fraction, we can find the greatest common divisor (GCD) of the numerator and denominator. In this case, the GCD is 48.
So, we can divide the numerator and denominator by 48:
(9408 / 150) = (9408/48) / (150/48) = 196/25

Therefore, (-3)/(3/4) * (2/7) * (-5/16) / (5/7) equals 196/25.